Sexual issues: let's hear it from the Malaysian boys - Low, Wah Yun; Ng, Chirk Jenn; Fadzil, Kamal Sohaimi; Ang, Eng Suan (Elsevier, 2007)
Background This paper explored adolescents’ sexuality with specific reference to their attitudes towards sex, safe sex, their risk-handling skills, sources of sexual information and how this information influenced their knowledge and attitudes.